Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ijerph192214809
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Cortisol Concentrations in Breastmilk and Its Associations with Breastmilk Composition and Infant Development in the First Six Months of Lactation

Abstract: Previous studies provided contradictory results regarding the influence of maternal, seasonal, and infant factors on breastmilk cortisol, and its associations with breastmilk composition and infant development. This study aimed to assess breastmilk cortisol levels at the first, third, and sixth months of lactation and evaluate the associations with maternal psychosocial, seasonal, and infant factors, breastmilk composition, and infant anthropometric and psychomotor development and temperament. Cortisol concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…However, our findings indicated no significant association. The findings reported in our study are similar to a study of healthy term infants in whom HM cortisol had no impact on temperament or neurodevelopment ( 76 ). We also did not detect any associations between maternal stress and the infant TIMP score.…”
Section: Discussionsupporting
confidence: 90%
“…However, our findings indicated no significant association. The findings reported in our study are similar to a study of healthy term infants in whom HM cortisol had no impact on temperament or neurodevelopment ( 76 ). We also did not detect any associations between maternal stress and the infant TIMP score.…”
Section: Discussionsupporting
confidence: 90%
“…For insulin, a lone study found no correlation between maternal age and insulin levels in human milk. Two studies explored the association between maternal age and cortisol, with both studies observing no correlation ( 28 , 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of insulin, Chan et al ( 12 ) reported higher levels in Asian mothers compared to Caucasians, while another study found no association with maternal carbohydrate and energy intake ( 12 ). For cortisol, Romijn et al ( 30 ) noted lower levels in mothers seeking psychiatric consultation compared to healthy controls, and another study found no association with postpartum depression score or perceived stress ( 41 ). Pundir et al ( 41 ) observed no association between mode of delivery and cortisol levels at 3 months.…”
Section: Resultsmentioning
confidence: 99%
“…Among many of the bioactive factors, breast milk contains glucocorticoids (GCs): cortisol, cortisone, and corticosterone GCs are transferred to BM through simple diffusion [78]. In studies, increased breast milk cortisol concentrations in the first 12 weeks of an infant's life were found [79].…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…However, some studies found that milk cortisol is positively associated with pro-inflammatory responses to some bacteria in vitro [83]. Animal studies also suggest that cortisol may improve intestinal development in both the microbiome and intestinal immune system [78].…”
Section: Glucocorticoidsmentioning
confidence: 99%